O papel do pai na família com bebê hospitalizado em unidade neonatal - Figueira, Maria Alice Barata dos Santos (2020)
The birth and immediate hospitalization of a preterm new born is a moment of suffering for the whole family. Much is researched and talked in what concerns the mother-baby relationship in the early moments of the newborn's life, and the difficulties of preterm birth. However, facing this context of the baby's birth, what would be the father's role? The research aims to observe the behaviour and feelings of the fathers of newborn babies hospitalized in a neonatal unit. The specific objectives consist of observing how the father behaves in relation to his baby in the neonatal unit; how the father feels when he experiences the baby's hospitalization; the father's feelings towards the baby's mother; and the father's feelings towards the institution's health professionals. The study proposed to be a qualitative research of an interpretative character, having psychoanalysis as its theoretical reference. Twenty interviews were conducted with parents of preterm babies admitted to the Conventional Intermediate Care Unit (UCINCo), a member of the Neonatal Unit - Kangaroo Method of the Professor Fernando Figueira Institute of Integral Medicine (IMIP). The analysis of the interviews was carried out using the content analysis method as proposed by Laurence Bardin. Two categories were identified: the construction of the father-baby bond and the experience of hospitalization, being a father in the hospital. In the first category, nine themes were analysed: ambivalent feelings; negative feelings; positive feelings; baby that cheers up the father; ways of caring; baby's father and mother relationship; father as a facilitator of the mother-baby relationship; changes; and being a father, being a man. In the second category, four themes were analysed: positive relationship with the team / institution; negative relationship with the team / institution; support network; and hospitalization context. The interviewed parents seemed to participate actively in the care of babies, accounting the differences in relation to the mothers’ care, but finding their way of exercising their role. The Winnicottian theoretical basis about the paternal function seems to be in agreement with what was found in the context of birth, in which the baby needs to be hospitalized. It was observed, more evidently, the paternal function, at the beginning of the baby's life, as the function of maternal substitute and facilitator to the mother-baby relationship